TANGGUNG JAWAB NEGARA TERHADAP ORANG ASING MENURUT HUKUM INTERNASIONAL DAN HUKUM NASIONAL INDONESIA - Siti Sarra; Sutiarnoto Sutiarnoto; Jelly Leviza (Journal of USU International Law, 2017)
RESPONSIBILITIES OF STATE TO PEOPLE BY INTERNATIONAL LAW AND INDONESIAN NATIONAL LAW Abstract Siti sarra* Sutiarnoto** Jelly leviza*** As the subject of International Law, countries have international rights and obligations. The state's responsibility to the individual is substantially determined by that country's territory and the nationality of the individual concerned. As for the problem in this research is how the protection against foreigners based on national law,how to protect foreigners under international law, and how the state is responsible for foreigners according to international law, with the title "Responsibility of the State Against Foreigners under International Law and Indonesian National Law". This research is a normative juridical research with descriptive nature. The data used in this study are primary legal materials, secondary legal materials, and tertiary legal materials. Data collection method used is literature study.Data analysis is done qualitatively. Legal protection for foreigners under national law can be found in Law Number 6 Year 2011 on Immigration, Law Number 16 Year 2009 on Ratification of Protocol Against the Smuggling of Migrants by Land, Sea and Air, Supplementing the United Nations Covention Against Transnational Crime, and Law Number 6 Year 2012 on Legalization International Convention on the Protection of the Rights of All Migrant Workers and Members of their Families. Legal protection for foreigners under national law can be found in the Montevideo Convention of 1993, The United Nations Declaration on Human Rights, dan The International Covenant on Civil and Political Rights. The state's responsibility to foreigners under international law is laid down in Draft Article on Responsibility of States for Internationally Wrongful Acts consisting of International Minimum Standard and National Minimum Standard, so that the state is responsible for the good treatment of its citizens or foreign nationals without any discriminatory state treatment in order to achieve equal legal protection. Key Words : Responsibility of State, Foreigner, National Law.